Al-Ḥarakah al-Fikrīyah wa al-Turāth ‘Inda al-Shaykh Ihsan Jampes Kediri: Mulāḥaẓah Tamhīdīyah - Barizi, Ahmad (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2004)
This paper tries to present an early discussion on tradition and intellectual movement of Kyai Ihsan Jampes, which has not been intellectually discussed. From various legitimate sources, there are 12 religious work written by Kyai Ihsan Jampes, both in printed forms and manuscript. It worth noted, different from general works of ulama in the Malay-Indonesia world, Kyai Ihsan Jampes had never learned Islam from Middle East ulama. He had only visited Mecca and Medina, which are the center of Islamic knowledge, once. And it was purely for pilgrimage purposes. However, this did not prevent him to be a productive writer.DOI: 10.15408/sdi.v11i3.598